Vigdis Broch-Due, Ingrid Rudie & Tone Bleie (eds.): Carved Flesh/Cast Selves: Gendered Symbols and Social Practices - Sørensen, Bo Wagner (Tidsskriftet Antropologi, 2019)
Vigdis Broch-Due, Ingrid Rudie & Tone Bleie (eds.): Carved Flesh/Cast Selves: Gendered Symbols and Social Practices Anmeldes af Bo Wagner Sørensen